2015
DOI: 10.17660/actahortic.2015.1083.49
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Concentrations of Nano-Silver on Elimination of Bacterial Contaminations and Phenolic Exudation of Rose (Rosa Hybrida L.) in Vitro Culture

Abstract: Rose is known as the first and the most important cutflowers in all over the world. One of the common methods of mass production of this plant is propagation through tissue culture. The main limiting factor of rose tissue culture is Bacterial contaminations and phenolic exudation in the establishment phase that significantly makes most of explants spoiled. Nano-Silver is able to control and stop the bacterial contamination. In this experiment Nano-Silver was added to medium with concentrations of (, , and ppm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 6 publications
0
13
0
2
Order By: Relevance
“…Shoot proliferation is influenced by several factors, such as genotype, media composition (Ruzic and Vujovic, 2008; Ivanova and Van Staden, 2009; Yang et al, 2012), disinfection and establishment methods (Shokri et al, 2013; Arab et al, 2014), in vitro environmental factors, etc. Development of an appropriate culture medium for a specific crop can be quite complex because the response to the culture medium is often genotype dependent, and the effects of mineral nutrition on morphogenesis have hardly been studied (Ramage and Williams, 2002; George et al, 2008; Greenway et al, 2012; Wada et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Shoot proliferation is influenced by several factors, such as genotype, media composition (Ruzic and Vujovic, 2008; Ivanova and Van Staden, 2009; Yang et al, 2012), disinfection and establishment methods (Shokri et al, 2013; Arab et al, 2014), in vitro environmental factors, etc. Development of an appropriate culture medium for a specific crop can be quite complex because the response to the culture medium is often genotype dependent, and the effects of mineral nutrition on morphogenesis have hardly been studied (Ramage and Williams, 2002; George et al, 2008; Greenway et al, 2012; Wada et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While addition to the MS medium 400 mg • dm -3 of nano-silver decreased the number of bacterial contaminations from 81.25% to 18.75%. Shokri et al (2014) showed, that adds to the MS medium 100 ppm of nano-silver decreased the number of bacterial contamination from 70% to 17.5%, and 87.5% rose (Rosa hybryda L.) explants were able to developed shoots. In addition, submerging of rose explants in 200 ppm of nano-silver solution for 20 minutes showed the best disinfection efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, submerging of rose explants in 200 ppm of nano-silver solution for 20 minutes showed the best disinfection efficiency. According to Shokri et al (2014) adding nano-silver to the MS medium allowed to obtain the highest efficiency of disinfection with the higher explants regeneration rate with a comparison to the submerging method. In the present study, we demonstrated the influence of nano-silver on the morphological traits of spring barley (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations